The Relationship Between Financial Reporting Practices and the 1986 Alternative Minimum Tax. - Wang, Shiing-wu (The Accounting Review, 1994)
Abstract Examines the effect of the book income adjustment on financial reporting using a modified research design. Effect of shifting accounting accruals on the alternative minimum tax (AMT) in 1987.